Comparison of microvascular density in cervical carcinoma in relation to predictive pathohistological parameters - Mandić Aljoša; Ivković-Kapicl Tatjana; Gutić Bojana; Maričić Slobodan; Stevanović Nemanja; Šolajić Nenad; Nikin Zoran; Maksimović Tamara; Stevanović Tijana (Archive of Oncology)
Objective: The occurrence, development, invasion, and metastasis of tumors are closely linked to angiogenesis, which is reflected by tumor microvessel density. The aim is to analyze microvascular density (MVD) in groups of patients with high grade squamous intraepithelial lesions (H-SIL), and cervical carcinoma, and to compare MVD in relation to the degree of tumor differentiation, size, presence of lymphovascular invasion and lymph node metastases. Materials and methods: The study was retrospective, conducted on histopathological samples of 109 patients who underwent hysterectomy with/without adnexectomy. Patients were divided into two groups depending on the histopathological results: group A - patients with H-SIL, and B with cervical cancer. The control group included surgically treated patients with benign uterine diseases. Based on hematoxylin/eosine staining, representative sample was chosen for immunohistochemistry, and the analysis of CD34 antigen expression and measurement of MVD were done. Results: In order to subdivide groups according to the low (L) and high (H) MVD, in control, group A, and B, with mean MVDs 2.2; 9.85 and 17.19, respectively, a cut-off values were determined. In the control group, LMVD 100% was measured. There were 7 (21.21%) in group A and 29 patients (63.04%) in group B with HMVD. A statistically significant difference was confirmed by comparing HMVD and LMVD in cervical cancer patients with lymph nodes metastasis (p<0.029). In the subgroup of patients with other worse pathohistological prognostic factors, a tumor size greater than 2 cm, depth of stromal invasion >10 mm, infiltration of "isthmus" of the uterus, a difference with no statistical significance was confirmed. Conclusion: Invasive cervical cancers are characterised by a significantly higher mean values of MVD compared to H-SIL. Significantly more often, HMVD is associated with the presence of lymph node metastases and histopathological parameters of poor prognosis.